Computational Binding Study Hints at Ecdysone 20-Mono-Oxygenase as the Hitherto Unknown Target for Ring C-Seco Limonoid-Type Insecticides - Ramsés E. Ramírez; Ricardo E. Buendia-Corona; Ivonne Pérez-Xochipa; Thomas Scior (Molecules, 2024)
The insecticidal property of ring C-seco limonoids has been discovered empirically and the target protein identified, but, to date, the molecular mechanism of action has not been described at the atomic scale. We elucidate on computational grounds whether nine C-seco limonoids present sufficiently high affinity to bind specifically with the putative target enzyme of the insects (ecdysone 20-monooxygenase). To this end, 3D models of ligands and the receptor target were generated and their interaction energies estimated by docking simulations. As a proof of concept, the tetrahydro-isoquinolinyl propenamide derivative QHC is the reference ligand bound to aldosterone synthase in the complex with PDB entry 4ZGX. It served as the 3D template for target modeling via homology. QHC was successfully docked back to its crystal pose in a one-digit nanomolar range. The reported experimental binding affinities span over the nanomolar to lower micromolar range. All nine limonoids were found with strong affinities in the range of −9 < ΔG < −13 kcal/mol. The molt hormone ecdysone showed a comparable ΔG energy of −12 kcal/mol, whereas −11 kcal/mol was the back docking result for the liganded crystal 4ZGX. In conclusion, the nine C-seco limonoids were strong binders on theoretical grounds in an activity range between a ten-fold lower to a ten-fold higher concentration level than insecticide ecdysone with its known target receptor. The comparable or even stronger binding hints at ecdysone 20-monooxygenase as their target biomolecule. Our assumption, however, is in need of future experimental confirmation before conclusions with certainty can be drawn about the true molecular mechanism of action for the C-seco limonoids under scrutiny.